Indole-3-acetic acid as a cross-talking molecule in algal-bacterial interactions and a potential driving force in algal bloom formation - Cheng, Xueyu; Li, Xinyang; Tong, Mengmeng; Wu, Jiajun; Chan, Leo Lai; Cai, Zhonghua; Zhou, Jin (Frontiers in Microbiology, 2023)
Most signaling molecules are involved in inter-or intra-species communication, and signaling involving cross-kingdom cell-to-cell communication is limited. Howerver, algae and bacteria exchange nutrients and information in a range of interactions in marine environments. Multiple signaling molecules exist between algae and bacteria, including quorum-sensing molecules, nitric oxide, and volatile organic compounds. Recently, indole-3-acetic acid (IAA), an auxin hormone that is a well-studied signaling molecule in terrestrial ecosystems, was found to act as a cue in cross-kingdom communication between algae and bacteria in aquatic environments. To increase understanding of the roles of IAA in the phycosphere, the latest evidence regarding the ecological functions of IAA in cross-kingdom communication between algae and bacteria has been compiled in this review. The pathways of IAA biosynthesis, effects of IAA on algal growth & reproduction, and potential mechanisms at phenotypic and molecular levels are summarized. It is proposed that IAA is an important molecule regulating algalbacterial interactions and acts as an invisible driving force in the formation of algal blooms.